2022
DOI: 10.2147/vhrm.s358849
|View full text |Cite
|
Sign up to set email alerts
|

The Klippel-Trénaunay Syndrome in 2022: Unravelling Its Genetic and Molecular Profile and Its Link to the Limb Overgrowth Syndromes

Abstract: The Klippel-Trénaunay syndrome is an unusual syndrome of vascular and dermatologic manifestation in which patients demonstrate hemihypertrophy of the soft tissue and bones of one limb, cutaneous haemangiomas and varicosities in anatomically abnormal positions. Described in 1900 by two French physicians, the etiology remained unclear until recently, when evidence emerged that there was a genetic basis for this sporadic disorder. Genes that encoded pathological angiogenic factors and caused vascular dysmorphogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…4,11,12 Additionally, the PIK3CA gene has also been reported to be responsible from the genotype of some of the patients with CVLM. 1,13 Somatic mutations in PIK3CA cause many overgrowth syndromes (particularly Cloves, fibro adipose hyperplasia and megalencephaly-capillary malformation) that have recently been identified as the PIK3CA-related overgrowth syndromes. 14,15 Many types of cancer have been reported in individuals with CVLM.…”
Section: Discussionmentioning
confidence: 99%
“…4,11,12 Additionally, the PIK3CA gene has also been reported to be responsible from the genotype of some of the patients with CVLM. 1,13 Somatic mutations in PIK3CA cause many overgrowth syndromes (particularly Cloves, fibro adipose hyperplasia and megalencephaly-capillary malformation) that have recently been identified as the PIK3CA-related overgrowth syndromes. 14,15 Many types of cancer have been reported in individuals with CVLM.…”
Section: Discussionmentioning
confidence: 99%
“…Two French doctors, Maurice Klippel and Paul Trénaunay, demonstrated that three children suffered from cutaneous hemangiomatous lesions along with asymmetrical hypertrophy of soft tissues and bony components in the early 19th century, coining the term "nevus variquece osteohypertrophique" [5]. KTS is a rare syndrome characterized by capillary microvascular malformations and abnormal venous development, resulting in varicosities and hypertrophy of the bone and soft tissue [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…There are several genetic defects that contribute to KTS, including overexpression of the angiogenic factor VG5Q and a de novo supernumerary ring chromosome 18 [5,6]. Most cases are sporadic [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations